2012
DOI: 10.1093/nar/gkr1240
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide occupancy links Hoxa2 to Wnt–β-catenin signaling in mouse embryonic development

Abstract: The regulation of gene expression is central to developmental programs and largely depends on the binding of sequence-specific transcription factors with cis-regulatory elements in the genome. Hox transcription factors specify the spatial coordinates of the body axis in all animals with bilateral symmetry, but a detailed knowledge of their molecular function in instructing cell fates is lacking. Here, we used chromatin immunoprecipitation with massively parallel sequencing (ChIP-seq) to identify Hoxa2 genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 73 publications
(105 citation statements)
references
References 58 publications
(72 reference statements)
5
98
0
2
Order By: Relevance
“…S6B). Moreover, in E11.5 Hoxa2 mutant second arch the expression of both Bmp4 and Bmp5 is downregulated (Donaldson et al, 2012). Together with the expression pattern changes observed in temporally induced Hoxa2 mutants (Fig.…”
Section: Hoxa2 Binds To Bmp4 and Bmp5 Non-coding Regions In Second Phsupporting
confidence: 69%
See 4 more Smart Citations
“…S6B). Moreover, in E11.5 Hoxa2 mutant second arch the expression of both Bmp4 and Bmp5 is downregulated (Donaldson et al, 2012). Together with the expression pattern changes observed in temporally induced Hoxa2 mutants (Fig.…”
Section: Hoxa2 Binds To Bmp4 and Bmp5 Non-coding Regions In Second Phsupporting
confidence: 69%
“…Thus, Hoxa2 acts upstream of the BMP canonical signalling pathway during external ear morphogenesis. A recent study has reported a role for Hoxa2 in activating the Wnt-β-catenin signalling pathway in the second arch (Donaldson et al, 2012), in part through the regulation of Wnt5a expression, a gene that when inactivated in mouse affects external ear development (Qian et al, 2007). Altogether, these data uncover roles for BMP and Wnt signalling in instructing external ear morphogenesis downstream of Hoxa2; how these pathways interact remains to be determined.…”
Section: Towards An Understanding Of the Molecular Mechanisms Involvementioning
confidence: 96%
See 3 more Smart Citations